Bite injury related to oromandibular dystonia extending to the maxillary sinus: A case report. Issue 6 (November 2020) - Koma, Yoshiro; Fujimoto, Takehiro; Uejima, Shinji; Sato, Kotaro; Sugimoto, Keisuke; Yamaguchi, Satoshi; Ishikawa, Jun; Nambu, Kazuya; Hibi, Hideharu
Abstract: Jaw-closing oromandibular dystonia (JCOD) is a potential symptom of dystonia. Because aspects of its pathogenesis and effective treatment remain to be determined, treating JCOD is challenging. There are some reports that JCOD may lead to secondary tooth wear and temporomandibular joint dysfunction, but whether associated severe bruxism can cause maxillary sinusitis after a bite injury is unknown. Herein we report a case of maxillary inflammation involving maxillary sinusitis after JCOD associated with hypoxic encephalopathy. A 60-year-old woman with JCOD as a symptom of generalized dystonia was referred to our department due to gingival swelling and bleeding in the region of the bilateral maxillary molars. The gingiva of the bilateral maxillary molars had evidently been injured by the mandibular molars. Computed tomography revealed dense soft-tissue masses in the bilateral maxillary sinuses, and an alveolar bone defect. Maxillary sinusitis caused by a bite injury was diagnosed. Because conservative treatment was not effective, tooth extraction was performed under general anesthesia to control the inflammation. The bite wound and maxillary sinusitis improved postoperatively, and the JCOD was completely resolved 3 days after the operation. We surmised that abnormal sensory-motor linkages may have been the main cause of the JCOD. Three years have now elapsed since the surgery, and there has been no recurrence of JCOD and no oral complications. We suggest that JCOD should be treated, because pain and abnormal sensations in the oral region may be involved in its development.